PENGARUH JENIS BUSI TERHADAP EMISI GAS BUANG MESIN OTTO 1 SILINDER - Ida Bagus Rayhan Lovaryan Putra Wijaya; Abrar Riza; Steven Darmawan (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2022)
Exhaust emissions are a mix of different gases and particles emitted by vehicles when the engine is running. Cars emit a potent mix of exhaust gases, many of which have harmful effects. They include CO2¬¬¬, CO, NOx, SO2, HC, and Particulates. Pollutants from cars are linked to a range of health problems, from allergies and skin irritation to heart disease and respiratory problems. Exhaust emissions correlated heavily with spark plugs. Spark plug is a device that fits into the cylinder head of an internal combustion engine and carries two electrodes separated by an air gap, across which current from a high tension ignition system discharges, to form a spark for igniting the air-fuel mixture. For determining the effects of types of spark plugs to emissions, the test is carried out on the honda GX 160 engine to compare nickel alloy and iridium spark plugs. The engine will be tested at 1800, 2100, 2400, 2700 and 3000 RPM to compare the exhaust emission emitted by the exhaust.